Chitin / Chitosan and alginates based two component systems for Fe3+ adsorption - Nwokeji, Chidozie Kingsley (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: In this study chitin and chitosan were blended with sodium alginate. The blends were characterized by FTIR and SEM analysis. The swelling ratios of obtained products in different pH (1.0, 7.0, 11) were determined and their adsorption properties in pH=1.3 were tested for Fe3+. The desorption capacities of the products in acidic buffer (pH=1.2) and alkaline media (0.06 M ammonia) were also compared. Chitin/Alginate and Chitosan/Alginate beads which swelled in aqueous media up to 200-300% were obtained. The beads proved to be effective Fe3+ adsorbents. Chitin/Alginate and Chitosan/Alginate beads showed an adsorption capacity of the order of 80mg/g bead towards Fe3+ in 100ppm Fe3+ solution within 3hours contact time. Ammonia (0.06M) was found to work better than acid buffer as a desorption agent for Fe3+. It was possible to obtain 100% desorption using ammonia solution. Keywords: Chitosan, alginic acid, Fe3+ adsorption. ………………………………………………………………………………………………………………………… ÖZ: Bu çalışmada, kitin ve kitosan aljinat ile karıştırılmış olup fiziksel özellikleri FTIR ve SEM analizleri ile karakterize edilmiştir. Elde edilen ürünlerin farklı pH lardaki tampon çözeltilerde (pH=1.0, 7.0, 11.0) şişme oranı belirlendi ve adsorpsiyon özellikleri, pH=1.2 Fe3+ için test edildi. Asidik tampon çözeltide (pH=1.2) ve alkali çözeltide (0.06 M amonyak) desorpsiyon kapasiteleri karşılaştırıldı. Sulu ortamda 200-300 % mertebesinde şişme kapasitesine sahip kitin/aljinat küreler elde edilmiştir. Ürünlerin 100 ppm Fe3+ çözeltisinde 3 saatte 80 mg Fe3+/g küre adsorplama kapasitesine ulaşabildikleri gözlemlenmiştir Seyreltilmiş amonyak çözeltisi ile 100% desorpsiyon sağlanabildiği saptanmıştır. Anahtar Kelimeler: Kitosan, aljinik asit, Fe3+ adsorpsiyonu.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2013. Supervisor: Prof. Dr. Elvan Yılmaz.
Keywords: Chemistry; Chitosan; Chitosan, Alginic Acid, Fe3+ Adsorption